Pemanfaatan Limbah Rumah Tangga Anorganik - Muhammad Fodhil; Muhammad Miftahudin; Heni Zuli Astutik; Abu Naim (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to find out the utilization of organic household waste. The approach method for the implementation of community service activities kkn-ppm padaskema includes workshop methods (training) discussions, and question and answer, this method is done so that the community, especially the youth get knowledge how to process inorganic waste, from unused goods to something that can be of economic value, and also the impact of waste care itself will create a clean and healthy environment..